Evaluation of Neuroinflammatory and Neurocognitive Effects of Noninvasive Ventilation Modes in COVID-19 Patients (Global Journal of Medical Research, 2022)
Background and Aim: Coronavirus disease (COVID-19) is a fatal disease that affects all systems, especially the pulmonary system and can effect pulmono-cerebral interaction. In this study, we compared the effects of High- Flow Nasal Cannula Oxygen (HFNC) and Non-Invasive Mechanical Ventilator (NIMV) use on COVID-19 severity scales and neuroinflammatory parameters and determine its relevance on the cognitive system. Material and Methods: This study was conducted on 50 patients using HFNC (n:25) or NIMV (n:25), who were followed up with COVID-19 pneumonia in the Neurology Intensive Care Unit (ICU) during September 2020. Demographic data, COVID-19 severity scales (Brescia-COVID Respiratory Severity Scale (BCRSS), Rapid COVID-19 Severity Index (QCSI), H-Index), serum neuroinflammatory parameters, Coronavirus Anxiety Scale (CAS) and Montreal Cognitive Assessment Scale were evaluated and compared on the first and seventh days in both groups. In addition, evaluation of thorax computed tomography (CT) findings, calculation of Total Lung Severity Score (TLSS) were determined.
Keywords: Cognitive assessment; COVID-19 pneumonia; HFNC; NIMV